Turvuus – kohti uutta turvallisuusymmärrystä - Silvasti, Markus (Tiede ja ase, 2017)
Security. Comprehensive security. Holistic security. Global security. Cosmic security. (In)security. It is di cult to follow current security thinking. New concepts are mushrooming to widen and deepen the (mis)understanding of security such as the concepts ‘crime security’ and ‘pandemic security’ demonstrate. is article will focus on conceptual understanding of security. Based on constructivistic approach the concept of security will be analysed to identify the main characteristics of security. As a conclusion this article will propose to desecuritize current security thinking by abandoning the current concept of security as too wide, fully politicized and analytically useless concept. New security thinking should be based on understanding where usual risks and uncertainties shape human life as condito humana. Instead of focusing on security we have to focus on nonchalance, freedom of (security) concerns to promote western ideal of good life.